Avaliação da qualidade da assistência à mulher e ao filho durante o parto normal - Carvalho, Isaiane da Silva (2014)
The practices developed in the everyday life of obstetric services are sometimes out of step with the recommendations of the public health policies. Accordingly, this research had the objective of assessing the quality of the care provided to women and children during cases of natural childbirth in municipal public maternity wards of the city of Natal/RN, Brazilian Northeast. We developed a cross-sectional and quantitative study in two maternity wards that provide care actions to pregnant women at regular risk (maternity wards A and B). The participants were 314 puerperal women who were treated during the period between April and July 2014, whose children were born alive, through transpelvic way, with spontaneous or induced beginning of labor and that showed physical and emotional conditions to respond to the proposed questions. The data collection instrument was constructed on the basis of the recommendations of the World Health Organization focused on the care of normal childbirth and validated by skilled judges, and the final version has obtained optimum agreement (k = 0,96; IVC = 0,99). Associated with these recommendations, we used three indicators: percentage of women with induced labor or subjected to elective cesarean section (Indicator A); percentage of women served by a qualified health professional during labor and childbirth (Indicator B); and Bologna Index (Indicator C). The research obtained a favorable opinion of the Research Ethics Committee from the Federal University of Rio Grande do Norte, under the nº 562.313 and Certificate of Presentation for Ethics Appreciation: 25958513.0.0000.5537. The analysis of categories related to the recommendations of the World Health Organization was conducted by means of absolute and relative frequency and the Chi-square Pearson’s and Fisher’s exact tests made the comparison of the differences observed between the two maternity wards. Furthermore, we calculated the percentage of the indicators A and B and with the results of the Indicator C, the quality was assessed as follows: the closer to 5, the better will be the quality, and the closer to 0, the worst will be the quality, and the Mann-Whitney U test was used to compare the differences of the obtained averages. The significance level of 5% was considered in all statistical tests. The differences between the maternity wards were identified with regard to the provision of liquids orally (p=0,018), stimulus for non-supine positions (p=0,002), existence of partograph (p=0,001), support or welcoming by health professionals (p= 0,047), intravenous infusion (p<0,001), supine position (p<0,001), use of oxytocin (p<0,001), food and liquid restriction (p= 0,002) and, lastly, the fact of the touch is performed by more than 1 examiner (p=0,011). The indicators A and B showed percentages of 13,09% and 100%, respectively. The overall average of the Indicator C was equal to 2,07 (± 0,74). There was a statistically significant difference between the averages of the maternity wards (p<0,001). The care actions provided during the process of labor and childbirth is inappropriate, especially in the maternity ward B. It is necessary to implement improvements and redesign the obstetric model in force